SISTEM DINAMIS KETERSEDIAAN DAGING SAPI DI PROVINSI BALI - Yulastari, Ni Made Evi; Satriawan, I Ketut; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): Desember, 2018)
The demand for beef in Bali Province is very high and dominated with hotels, restaurants, and cafes. The purpose of this research is to know the factors that influence the availability of beef, analyze the availability of beef, and make alternative policy recommendation that can be done in order to meet the demand of beef. This research was conducted in Bali Province using system dynamic approach. Simulation are conducted over a period of 10 year, starting from 2012 until 2021. Factors affecting beef availability is beef production and beef demand. Simulation results show that beef production in Bali Province has not been able to meet the demand of beef. The availability of beef in Bali Province tended to decline from the beginning of the simulation year to the end of the simulation year. Based on the simulation results of several scenarios, the most effective and possibly developed policy to meet the needs of beef is through the efforts of fattening cattle. Key words : dynamic system, availability, beef, simulation s